EVALUASI EFEKTIVITAS PENERAPAN SISTEM AKUNTANSI PENGELUARAN KAS ATAS UANG PERSEDIAAN (UP) PADA DINAS PERTANIAN DAN PETERNAKAN PROVINSI SULAWESI UTARA - Polii, Betriana Frisly; Mawikere, Lidia (Universitas Sam Ratulangi, 2015)
The role of local governments that manage their own regional finance in an effort to optimize the revenue potential of each region in order to enhance the development of the area. This study aims to determine the application of the accounting system of cash expenditure on Money Supply (UP) in the Department of Agriculture and Animal Husbandry of North Sulawesi Province. The method used is descriptive qualitative. The results showed the implementation of the accounting system of cash expenditure on the money supply in the Department of Agriculture and Animal Husbandry of North Sulawesi province has been conducted in accordance with the theory of cashexpenditure accounting system as well as the existing rules. Expected training in accounting in order to process performance can be run as expected.